Unsteady migration of Taebaek Mountain drainage divide, Cenozoic extensional basin margin, Korean Peninsula - Kim, Dong-Eun; Seong, Yeong Bae; Weber, John; Yu, Byung Yong (ELSEVIER, 2020)
The Taebaek Mountain Range (TBR) initially formed via extension of a back-arc basin in the East Sea during the early-Miocene (ca. similar to 22 Ma) and exemplifies a typical escarpment on a passive continental margin. The TBR acts as a major watershed and divide across which topography changes from gentle western side slopes to steep eastern slopes. Compared to the geologic history of the flanking extensional basin, which is well known from analysis of its sedimentary fill, the post-extensional geomorphic history of the escarpment and basin margin has been minimally studied because of a lack of terrestrial archives. We determined the rate and cause of divide migration of the TBR using a suite of relatively new geomorphic and geochronologic tools. We used geomorphic analyses of relief, slope, river long profiles, swath profiles, and chi parameters to study this transient topography. Catchment-wide denudation rates (CWDR) using Be-10 facilitated comparisons of denudation rates of cross-divide paired basins. Denudation rates east of the divide from drainages with steep slopes average nearly two times counterparts with gentle slopes west of the divide. Gilbert metrics used to assess divide mobility strongly suggest that catchments in the eastern TBR may have captured counterpart catchments in the west. Both CWDR and Gilbert metric results reveal that retreat of the main TBR divide likely accelerated in the late Quaternary following tectonic inversion, surface uplift, and tilting or flexure in the eastern TBR. Geomorphic disequilibrium across the current divide of the TBR continues until the present (C) 2019 Elsevier B.V. All rights reserved.